Youth concepts regarding child participation and children's right - Ramírez Pavelic, Mónica (2015)
We present the results of an investigation which aim is to analyze – in the words of young university students – their conceptions regarding child participation in the context of the International Convention on the Rights of the Child. To that end, it featured the informed participation of 53 university students in 1st year of Psychology at a Spanish university, whose ages were 18 years old. They formed four discussion groups; and for the processing and analysis of the information, the QDA Miner software and discourse analysis were used. The main findings indicated that among our interviewed, exists a perception of low participation of children, in addition to scarce knowledge regarding the rights of the child.